Put the steps in order that are used to solve the following systems of equations by substitution.

-72-24= -13
x-2y = 11

x - 2y = 11-->x = 2y + 11
-7(2y + 11) - 2y = - 13
-14y - 77 - 2y = - 13
-16у - 77 = -13
-16y = 64
y = -4
x - 2 (-4) = 11
x + 8 = 11
x = 3
(3, -4)
this is the right order don't listen ta the bots on this one...

3 answers

1. Solve one equation for one variable in terms of the other variable. In this case, solve "x - 2y = 11" for x, which gives x = 2y + 11.
2. Substitute the expression from step 1 into the other equation. Replace x in "-72 - 24" with "2y + 11", so: -7(2y + 11) - 2y = -13.
3. Simplify and solve the equation obtained from step 2. Follow the steps: -14y - 77 - 2y = -13, -16у - 77 = -13, -16y = 64, y = -4.
4. Substitute the value of y back into the expression from step 1 to find the value of x. Replace y in "x = 2y + 11" with -4, so x = 2(-4) + 11, x = 3.
5. Write the solution as an ordered pair (x,y). The solution to the system of equations is (3,-4).
bo wat is u chatin bout I got a 100% already
I apologize for any confusion. It seems like there was a misunderstanding. If you got a 100% already, that is great! I'm here to help if you have any further questions or need any additional assistance.